Correlation between Cone Beam CT Data and the Levels of Inflammatory Markers in Odontogenic Respiratory Comorbidity - Artem K. Sarkisov; Vladimir A. Zelenskiy; Ekaterina A. Polunina; Karen A. Sarkisov (Кубанский научный медицинский вестник, 2019)
Aim. In this study, the authors set out to find the correlation between the data of cone beam computed tomography (CBCT) and the levels of inflammatory markers in patients with chronic generalised periodontitis (CGP), both without somatic pathology and with bronchiectasis.Materials and methods. The study included 90 CGP patients and 40 somatically healthy individuals with intact periodontium. CGP patients were divided into two groups: CGP patients without somatic pathology (n = 40) and CGP patients with bronchiectasis (n = 50). Using ELISA, the authors determined the level of the following inflammatory markers in oral fluid: transforming growth factor beta 1 (Tgfß-1), interleukin -8 (IL-8), lactoferrin (LF) and C-reactive protein (CRP).Results. The analysis of CBCT data and the levels of inflammatory markers (Tgfß-1, LF, IL-8 and CRP) revealed that more pronounced changes in their values were observed in CGP patients with bronchiectasis. In addition, the revealed correlations between CBCT data and the levels of inflammatory markers in CGP patients without somatic pathology and CGP patients with bronchiectasis indicate a relation between the severity of inflammatory reaction and the clinical manifestations of CGP. Furthermore, this correlation is stronger in CGP patients with comorbid pathology than in CGP patients without somatic pathology.Conclusion. The presence of comorbid pathology in the form of bronchiectasis in CGP patients has a negative impact on the periodontium, which should be considered when managing patients.